2005
DOI: 10.1163/1568537054068660
|View full text |Cite
|
Sign up to set email alerts
|

Linkages between Number Concepts, Spatial Thinking, and Directionality of Writing: The SNARC Effect and the REVERSE SNARC Effect in English and Arabic Monoliterates, Biliterates, and Illiterate Arabic Speakers

Abstract: The current investigations coordinate math cognition and cultural approaches to numeric thinking to examine the linkages between numeric and spatial processes, and how these linkages are modified by the cultural artifact of writing. Previous research in the adult numeric cognition literature has shown that English monoliterates have a spatialised mental number line which is oriented from left-to-right with smaller magnitudes associated with the left side of space and larger magnitudes are associated with the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
269
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(286 citation statements)
references
References 0 publications
13
269
1
3
Order By: Relevance
“…It refers to the observation that participants are faster to respond to small numbers with left-hand responses compared to right-hand responses, and faster to respond to large numbers with their right hand than with their left hand. According to Dehaene et al (1993), this interaction between numbers and space is directly related to the left-to-right orientation of the metaphorical mental number line (smaller numbers on the left, larger numbers on the right), and they suggested that this specific orientation is formed by cultural factors such as general writing direction (see also Zebian, 2005). All the numerical effects described before are a result of the representation that underlies them.…”
Section: Similar Effect Patterns With Different Kinds Of Quantity: Thmentioning
confidence: 95%
“…It refers to the observation that participants are faster to respond to small numbers with left-hand responses compared to right-hand responses, and faster to respond to large numbers with their right hand than with their left hand. According to Dehaene et al (1993), this interaction between numbers and space is directly related to the left-to-right orientation of the metaphorical mental number line (smaller numbers on the left, larger numbers on the right), and they suggested that this specific orientation is formed by cultural factors such as general writing direction (see also Zebian, 2005). All the numerical effects described before are a result of the representation that underlies them.…”
Section: Similar Effect Patterns With Different Kinds Of Quantity: Thmentioning
confidence: 95%
“…In countries where people read and write from right to left, SNARC effects reflect mental number lines directed horizontally from right to left. This means that responses to relatively smaller numerals are carried out faster on the right side, whereas responses to relatively bigger numerals are carried faster on the left side Zebian 2005). Some authors have investigated the relationship between the writing direction of digits and SNARC effects.…”
Section: The Cultural Factors Of the Flexibility Of Snarc Effectsmentioning
confidence: 99%
“…One is compatible with the direction of the mental number line -that is, the smaller digit is on the left and the larger digit is on the right-while the other is in the opposite direction. The participants were asked to indicate the larger or smaller numeral (Fischer 2003;Shaki and Petrusic 2005) or to evaluate whether the values of exhibited numerals were equal or different (Zebian 2005). Indicators of SNARC effects in such a research framework are: shorter reaction times to a double numeral stimulus arranged in accordance with the direction of the number line; and longer reaction times to a double numeral stimulus arranged in a way opposite to the direction of the axis.…”
Section: The Way Numeral Stimuli Are Spatially Arrangedmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect, called SNARC (Spatial-Numerical Associations of Response Codes, Dehaene, Bossini, & Giraux, 1993), is considered as the most prominent effect that shows that number processing can be oriented in space (for reviews see Gevers & Lammertyn, 2005;Wood, Willmes, Nuerk, & Fischer, 2008). A particular orientation of SNARC is mostly attributed to the direction of language orthography in a given culture: Whereas the left-to-right/small-to-large association is usually observed in left-to-right reading societies (Western countries), this association reverses or disappears in right-to-left reading cultures (Middle-Eastern countries, Dehaene, Bossini, & Giraux, 1993;Rashidi-Ranjbar, Goudarzvand, Jahangiri, Brugger, & Loetscher, 2014;Shaki & Fischer, 2008;Shaki, Fischer, & Petrusic, 2009;Zebian, 2005).…”
Section: Introductionmentioning
confidence: 99%